Rapidly Enlarging Neck Mass in a Neonate Causing Airway Compromise. Issue 2 (1st April 2016) - Schmidt, Kyra; Leal, Andres; Mcgill, Thomas; Jacob, Roy
Abstract : Up to 20% of all congenital pediatric head and neck masses are branchial cleft cysts. Second branchial cleft cysts account for 95% of branchial anomalies, and fourth branchial cleft cysts are the rarest type. Their typical presentations include non–life–threatening symptoms, such as drainage, skin irritations, minor swelling, and tenderness. We describe a 5-week-old neonate with increasing stridor secondary to a rapidly growing neck mass. Imaging and surgical excision confirmed the mass to be an infected fourth branchial cleft cyst.